Small airway function before and after cold dry air challenge in pediatric asthma patients during remission. Issue 7 (9th May 2017) - Steinbacher, Michael; Pfleger, Andreas; Schwantzer, Gerold; Jauk, Stefanie; Weinhandl, Elisabeth; Eber, Ernst
Abstract: Background: We wanted to compare cold dry air challenge (CACh) induced changes in spirometric parameters with changes in nitrogen multiple breath washout (N2 MBW) parameters in pediatric asthma patients during clinical remission over the past year (ie, with "inactive asthma"). As N2 MBW assesses ventilation heterogeneity we expected to gain detailed information about peripheral airways contribution. Methods: In subjects with normal spirometry N2 MBW, spirometry and body plethysmography were performed at baseline, after CACh, and after salbutamol inhalation. An initial measurement of the fraction of exhaled nitric oxide (FeNO) was conducted. Results: Forty‐three (20 female) subjects, mean age 13.7 years (range 6.5‐18.6) performed reproducible N2 MBW measurements. Ten were tested hyperresponsive (23.3%) and 33 normoresponsive (76.7%). Baseline spirometry and body plethysmography as well as FRC (N2 MBW) were similar in both groups. Scond (0.031 vs 0.022), Sacin (0.057 vs 0.067), and FeNO (92.0 vs 28.5 ppb) were not statistically different between hyperresponsive and nomoresponsive subjects at baseline. Subjects with airway hyperresponsiveness (AHR) showed significant increases in lung clearance index (LCI, P  = 0.011) and Scond ( P  = 0.008) after CACh, and significant decreases after salbutamol (LCI: P  = 0.005; Scond: P  = 0.005). In contrast, normoresponsive subjects showed no relevant changes after CACh, and only a decrease of Scond after salbutamol ( P  = 0.007). There were significant correlations between the CACh induced changes in FEV1 and changes in LCI ( r  = −0.45, P  = 0.003), Scond ( r  = −0.30, P  = 0.047), and Sacin ( r  = −0.47, P  = 0.008), respectively. Conclusion: Our study provides evidence of small airway involvement in children and adolescents with inactive asthma and airway hyperresponsiveness.